2013
DOI: 10.1155/2013/648141
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Dependant Assessment, Diversity, and Ecology of Haloalkaliphilic Bacteria in Arid Saline Systems of Southern Tunisia

Abstract: Haloalkaliphiles are polyextremophiles adapted to grow at high salt concentrations and alkaline pH values. In this work, we isolated 122 haloalkaliphilic bacteria upon enrichments of 23 samples from 5 distinct saline systems of southern Tunisia, growing optimally in media with 10% salt and at pH 10. The collection was classified into 44 groups based on the amplification of the 16S–23S rRNA internal transcribed spacers (ITS-PCR). Phylogenetic analysis and sequencing of the 16S rRNA genes allowed the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 77 publications
2
21
0
Order By: Relevance
“…Moreover, representatives of the 11 genera were facultative alkaliphiles , tolerating the highest pH values. Several of the genera described in this study have been previously reported as halotolerant, for example Nesterenkonia isolated from southern Tunisia, Brazilian Mangrove sediment and hypersaline Ekho Lake in East Antarctica and Arthrobacter strains isolated from southern Tunisia . Alkaliphilic Streptomyces were likewise found in various types of soils of Georgia and in saline soils and lake sediments from China .…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, representatives of the 11 genera were facultative alkaliphiles , tolerating the highest pH values. Several of the genera described in this study have been previously reported as halotolerant, for example Nesterenkonia isolated from southern Tunisia, Brazilian Mangrove sediment and hypersaline Ekho Lake in East Antarctica and Arthrobacter strains isolated from southern Tunisia . Alkaliphilic Streptomyces were likewise found in various types of soils of Georgia and in saline soils and lake sediments from China .…”
Section: Discussionsupporting
confidence: 62%
“…Thirteen different taxonomic families divided into 16 genera were identified. The isolates affiliated to the genera Aliidiomarina (5), Alkalimonas (4), Bacillus (16), Cecembia (5), Halomonas (6), Nitrincola (5), Rhodobaca (2) and Vibrio (2) had already been found in similar halo-alkaline conditions [5255]. However, the 16S rRNA gene sequence analysis may have revealed new taxa (Table 5 and S1 Text).…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies on the composition of soil microbial diversity in saline soils revealed that soil salinization had negative effects not merely on soil biochemical properties, but also on the structure of microbial communities (Foti et al, 2007;Yuan et al, 2007;Hidri et al, 2013;Wang et al, 2014;Zhang et al, 2015). Regarding the soil microbial community in saline soils of Songnen Plain, only some representative new species of halophilic and halotolerant bacteria and archaea have been reported by pure culture methods (Wu et al, 2008;Wang et al, 2010;Liu et al, 2011b;He et al, 2014;Pan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%